CD147 Promotes Tumorigenesis via Exosome-Mediated Signaling in Rhabdomyosarcoma - Assil Fahs; Nader Hussein; Hasan Zalzali; Farah Ramadan; Farah Ghamloush; Hani Tamim; Mahmoud El Homsi; Bassam Badran; Fouad Boulos; Ayman Tawil; Sandra E. Ghayad; Raya Saab (Cells, 2022)
Rhabdomyosarcoma (RMS) is an aggressive childhood soft-tissue tumor, with propensity for local invasion and distant metastasis. Exosomes are secreted vesicles that mediate paracrine signaling by delivering functional proteins and miRNA to recipient cells. The transmembrane protein CD147, also known as Basigin or EMMPRIN, is enriched in various tumor cells, as well as in tumor-derived exosomes, and has been correlated with poor prognosis in several types of cancer, but has not been previously investigated in RMS. We investigated the effects of CD147 on RMS cell biology and paracrine signaling, specifically its contribution to invasion and metastatic phenotype. CD147 downregulation diminishes RMS cell invasion and inhibits anchorage-independent growth in vitro. While treatment of normal fibroblasts with RMS-derived exosomes results in a significant increase in proliferation, migration, and invasion, these effects are reversed when using exosomes from CD147-downregulated RMS cells. In human RMS tissue, CD147 was expressed exclusively in metastatic tumors. Altogether, our results demonstrate that CD147 contributes to RMS tumor cell aggressiveness, and is involved in modulating the microenvironment through RMS-secreted exosomes. Targeted inhibition of CD147 reduces its expression levels within the isolated exosomes and reduces the capacity of these exosomes to enhance cellular invasive properties.